2014
DOI: 10.1021/la5035678
|View full text |Cite
|
Sign up to set email alerts
|

Self-Aggregation of Sodium Dodecyl Sulfate within (Choline Chloride + Urea) Deep Eutectic Solvent

Abstract: Deep eutectic solvents (DESs) have shown tremendous promise as green solvents with low toxicity and cost. Understanding molecular aggregation processes within DESs will not only enhance the application potential of these solvents but also help alleviate some of the limitations associated with them. Among DESs, those comprising choline chloride and appropriate hydrogen-bond donors are inexpensive and easy to prepare. On the basis of fluorescence probe, electrical conductivity, and surface tension experiments, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 40 publications
3
73
0
1
Order By: Relevance
“…[27] Moreover, the possibility of microemulsion formation, by typical tensioactive compounds [28] or directly, [29] ensures, at least, the partial solubility of less polar organic reagents, which highlights the enormous ability of these mixtures as a possible medium in Organic Synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Moreover, the possibility of microemulsion formation, by typical tensioactive compounds [28] or directly, [29] ensures, at least, the partial solubility of less polar organic reagents, which highlights the enormous ability of these mixtures as a possible medium in Organic Synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…24 In subsequent studies a mixture of choline chloride:urea with water was found to promote the selfassembly of sodium dodecyl sulfate (SDS). 25 Cationic surfactants were also found to be soluble and form aggregates in choline chloride:glycerol, although no structural detail on such aggregates has yet been reported. 26 Tan et al have shown the self-assembly of long chain ionic liquids in choline chloride:glycerol DES.…”
Section: Introductionmentioning
confidence: 99%
“…类离子液体 对于金属盐类、 有机化合物等均具有良好的溶解性能, 不但可起到溶剂的作用, 而且对于不同的反应还可 起到模板剂、表面剂、催化剂、氧化还原剂和金属/ 碳源的作用. Pal 等 [42] 发现十二烷基磺酸钠可增强环 己烷在尿素-氯化胆碱类离子液体中的溶解性, 并形 成环己烷-类离子液体微乳液, 该类无水型微乳液的 形成提供了一种新型纳米反应器. Abo-Hamad 等 [43] 指出类离子液体在纳米孔道或管体等限域条件下可 表现出不同于宏观尺度下的行为.…”
Section: 类离子液体的应用unclassified